2010
DOI: 10.1021/es903521n
|View full text |Cite
|
Sign up to set email alerts
|

Gulf of Mexico Hypoxia: Exploring Increasing Sensitivity to Nitrogen Loads

Abstract: Hypoxia is a critical issue in the Gulf of Mexico that has challenged management efforts in recent years by an increase in hypoxia sensitivity to nitrogen loads. Several mechanisms have been proposed to explain the recent increase in sensitivity. Two commonly cited mechanisms are bottom-water reducing conditions preventing nitrification and thus denitrification, leading to more N recycling and production of oxygen-consuming organic matter, and carryover of organic matter from previous years increasing oxygen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 44 publications
(98 reference statements)
4
49
2
Order By: Relevance
“…Previous studies suggested no apparent correlation between hypoxic area (or predictive errors) in 1 y and either N load or hypoxic extent in the previous year. Thus, including predictors representing carryover effects from the previous year did not substantially improve model fit (31,35,69). The loads used by each model show similar interannual patterns (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…Previous studies suggested no apparent correlation between hypoxic area (or predictive errors) in 1 y and either N load or hypoxic extent in the previous year. Thus, including predictors representing carryover effects from the previous year did not substantially improve model fit (31,35,69). The loads used by each model show similar interannual patterns (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…We divided our correlation analysis into two periods: the longer was from 1985-2010, the shorter was from 1993-2010. The shorter period begins with 1993, i.e., the year in which the relationship between hypoxic area and riverine N-loading was reported to have changed [Turner et al, 2008;Greene et al, 2009;Liu et al, 2010;Forrest et al, 2011]. [7] The predictors in our single and multiple regression analyses are: the new variable t Uwind (defined below), the 11-month averaged MR flow ( F 11 ) [Wiseman et al, 1997], the averaged spring flow ( F spring ; April, May and June), the averaged May flow ( F May ) [Greene et al, 2009], the May NO 3+2 loading [Turner et al, 2006] and the combined MayJune NO 3+2 loading [Donner and Scavia, 2007].…”
Section: Methodsmentioning
confidence: 99%
“…Scavia et al [2003] reproduced the hypoxic area by using a one-dimensional model driven by the May-June total N-loading from the MAR. Liu et al [2010] improved the predictions of this model by incorporating an additional parameter to describe a system change in 1993. The above models were the basis of the hypoxia management strategy [Mississippi River/Gulf of Mexico Watershed Nutrient Task Force, 2001Force, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Scavia et al (2003), Scavia and Donnelly (2007), and Liu et al (2010). Calibration of parameters of the model by year has produced good fit to the observed hypoxia area (88 percent of variability explained in Scavia et al (2003), and 99 percent explained in Liu et al (2010) using Bayesian calibration techniques. All of these models focus on nitrogen.…”
Section: Linking the Size Of The Zone To Its Inputs: The Gulf Of mentioning
confidence: 99%